THE EFFECT OF VACCINATON ON COVID-19 DEATHS: A RESEARCH ACCORDING TO COUNTRIES' INCOME GROUPS - Durmuş Gökkaya; Osman Şenol; Ümit Çıraklı (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study aims to reveal the impacts of Covid-19 vaccination on Covid-19 based deaths in countries with different income levels. In this context, the study investigated data between 01.03.2021 and 08.08.2021 by Panel data analysis. In the research, firstly, countries were divided into three different categories according to income groups: low-income level, middle-income level and high-income level. Therefore, each country group was examined separately and three different econometric models were produced. According to the results of the research, a 1% increase in the population vaccinated will result in a 2.1% decrease in the number of deaths from Covid-19 in low-income countries, a 0.5% decrease in middle-income countries and a 13% decrease in high-income countries. According to the results of the research, it was concluded that vaccination will significantly reduce deaths from Covid-19. For this reason, it is recommended that people complete their vaccine doses as fast as possible.